Nitrogen Depletion Blocks Growth Stimulation Driven by the Expression of Nitric Oxide Synthase in Tobacco - Nejamkin, Andrés; Foresi, Noelia; Mayta, Martín L.; Lodeyro, Anabella F.; Castello, Fiorella Del; Correa-Aragunde, Natalia; Carrillo, Néstor; Lamattina, Lorenzo (Frontiers in Plant Science, 2020)
Nitric oxide (NO) is a messenger molecule widespread studied in plant physiology. Latter evidence supports the lack of a NO-producing system involving a NO synthase (NOS) activity in higher plants. However, a NOS gene from the unicellular marine alga Ostreococcus tauri (OtNOS) was characterized in recent years. OtNOS is a genuine NOS, with similar spectroscopic fingerprints to mammalian NOSs and high NO producing capacity. We are interested in investigating whether OtNOS activity alters nitrogen metabolism and nitrogen availability, thus improving growth promotion conditions in tobacco. Tobacco plants were transformed with OtNOS under the constitutive CaMV 35S promoter. Transgenic tobacco plants expressing OtNOS accumulated higher NO levels compared to siblings transformed with the empty vector, and displayed accelerated growth in different media containing sufficient nitrogen availability. Under conditions of nitrogen scarcity, the growth promoting effect of the OtNOS expression is diluted in terms of total leaf area, protein content and seed production. It is proposed that OtNOS might possess a plant growth promoting effect through facilitating N remobilization and nitrate assimilation with potential to improve crop plants performance.